A strategic approach to collaborative resource mobilization for climate change, agriculture and food security research, Findings from a MScCCAFS research project involving CCAFS Strategic Research Partners - Costelloe, Christine; Styles, David; McKeown, Peter; Engelund Friis, Anette; Campbell, Bruce M.; Spillane, Charles (2018)
CCAFS has a unique strategic partnership approach to address climate-related challenges facing agriculture in developing countries. CCAFS achieves impact and outcomes through its work with 42 Strategic Partners, 13 of which are CCAFS Strategic Research Partners. Additional financial resources are needed for CCAFS to achieve the impact and outcomes in its Phase II Full Proposal 2017–2022. Interviews with CCAFS Strategic Research Partners show that opportunities exist to further the co-creation of CCAFS knowledge and co-mobilization of funding and resources for CCAFS’ 2017–2022 research priorities by forming a more effective Community of Practice of CCAFS Strategic Research Partners. Combining resource mobilization capacity and objectives of CCAFS Strategic Research Partners can benefit both CCAFS and CCAFS Strategic Research Partners. Regular communication and planning are key attributes of an effective Community of Practice, which can be applied to engagement between CCAFS and its CCAFS Strategic Research Partners and between CCAFS Strategic Research Partners. Research shows that implementation of a funding roadmap and weekly planner could provide elements of a pathway for collaborative resource mobilization activities.